2013
DOI: 10.1007/s40069-013-0028-1
|View full text |Cite
|
Sign up to set email alerts
|

Advances on the Behavior Characterization of FRP-Anchored Carbon Fiber-Reinforced Polymer (CFRP) Sheets Used to Strengthen Concrete Elements

Abstract: Strengthening concrete structures using FRP composites is a commonly considered technology in many practical situations. The success of the strengthening intervention largely depends on adequate bond between FRP sheets and the concrete substrate. In recent years, techniques to anchor FRP sheets in applications where sheets must develop strength in a short length have been proposed. One of these techniques includes use of FRP anchors embedded into the concrete substrate and forming part of the composite strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…The CFRPs used have a length of 1100 mm and a width of 100 mm, and only two sides of the column section were strengthened with CFRPs. The presence of CFRPs was expected to improve the joint confinement and to avoid the failure of the CFRP anchors (Ozbakkaloglu and Saatcioglu 2009;Brena and McGuirk 2013). It is noted that in this study only one specimen strengthened with CFRPs was tested.…”
Section: Test Specimensmentioning
confidence: 96%
“…The CFRPs used have a length of 1100 mm and a width of 100 mm, and only two sides of the column section were strengthened with CFRPs. The presence of CFRPs was expected to improve the joint confinement and to avoid the failure of the CFRP anchors (Ozbakkaloglu and Saatcioglu 2009;Brena and McGuirk 2013). It is noted that in this study only one specimen strengthened with CFRPs was tested.…”
Section: Test Specimensmentioning
confidence: 96%
“…This issue is of great importance, as can be attested to by the numerous researches found in the literature (Biscaia et al 2014;Mendes 2008;Martinelli et al 2012;Breña and McGuirk 2013;Realfonzo et al 2013;Wu and Liu 2013) seeking for a valid and alternative solution for enhancing the strength of EBR systems. Still, it is important to bear in mind that the use of steel mechanical fasteners involves making a hole on the SS strip which may lead to an important setback due to the reduction of the SS cross section of the strip to install the fasteners.…”
Section: Definition Of the Effective Bond Lengthmentioning
confidence: 99%
“…roughout the 21 st century, research on FRP strip debonding failure has accelerated, as various anchor systems have been devised and tested in academia and industry [1][2][3][4][5]. One anchorage system is the FRP spike anchor, which is made of a tow of unidirectional fibers to be inserted into the predrilled holes in concrete, which can be pushed through to the other end of the tow where this relatively new FRP spike anchor spreads on top of the FRP to form a fan [6][7][8][9][10]. ese investigations have shown that this anchor system can improve the ultimate capacity [6] and can be used to prevent premature debonding of FRP sheets from concrete surfaces [7].…”
Section: Introductionmentioning
confidence: 99%
“…ese investigations have shown that this anchor system can improve the ultimate capacity [6] and can be used to prevent premature debonding of FRP sheets from concrete surfaces [7]. Llauradó et al [8] presented an analytical model to predict the anchoring behavior of the FRP spike anchor system; Breña and Mcguirk [9]and Teng et al [10] showed that the FRP spike anchor system can enhance both the capacity and ductility of FRP reinforced concrete members to some extent. Some metallic elements such as bolts and plates have also been used to anchor systems and have good applicability in improving capacity [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%